The Approach of the European Union Towards China’s Violation of Human Rights - Březinová, Klára; Garlick, Jeremy; Shakhanova, Gaziza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
Human rights are one of the core values of the European Union from its early start. It equally binds itself to promote and protect human rights while dealing with third party states on the international level. Therefore, the thesis aims to examine the EU’s position regarding China’s human rights abuses. Especially within its foreign policy approach. As the theoretical background constructivism, namely Nicolas Onuf’s conception was used. For the practical part, discourse analysis was used. Through three official discourses and two dialogues, the thesis tries to understand the application of the European policies in praxis. The chosen actors of the EU foreign policy were The President of the EC, Ursula von der Leyen and the Vice President of the EC and simultaneously the High Representative of the EU, Josep Borrell Fontelles. In the practical part, there have been analysed three discourses where the actors directly represent the EU at a press conference or as in the case of the President of the EC, once in front of the EP. For the High Representative of the EU, Borrell, there were furthermore added two discourses from dialogues held at external conferences. After presenting Onuf’s conception of constructivism, which the thesis is based on and the contextualisation of the actors’ role within the EU foreign affairs. The thesis briefly presents human rights issues in China and the official approach of the EU towards human rights abuses. The chosen China human rights issues are tackling the Nort-West province Xinjiang and digital freedom connected to the 5G communication. The EU stances are mostly derived from the EU official documents such as the ECHR, the Lisbon Treaty, European Action Plans and others. The biggest contribution of the thesis is incorporated in the fourth, respectively the fifth chapter.
The fourth chapter analyses separately the chosen discourses of the EU foreign affairs actors while the fifth chapter conjoins the findings of the fourth chapter. While the thesis main focus is put on the application of the EU’s human rights values into praxis. It further evaluates how the policies are mirrored in the discourses of the main two representatives’ discourses. The examined discourses took place from May 2020 to March 2021. It might seem from the official documents, that the EU puts equal importance on both, the values, and the EU’s interests. However, the analysed discourses show different. Likewise, detail and time donation was much higher connected to the EU’s economic interests and relations with China in comparison to the addressing of human rights issues. Moreover, it has been found out that within the human rights issues’ context, actors stressed primally human rights of EU citizens and discussed the prevention of potential human rights threats, as cyber-attacks, or digital spying. Lastly, the thesis’ finding is the relatively swift change of the approach towards human rights oppressions in the Xinjiang region.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses